2013
DOI: 10.3390/nano3010141
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Polycaprolactone on Oxidized Nanocelluloses by Click Chemistry

Abstract: The main objective of this work is the grafting of polycaprolactone diol (PCL) on the surface of oxidized nanocelluloses (ONC) in order to enhance the compatibility between the hydrophilic cellulose nanofibres and the hydrophobic polymer matrix. This grafting was successfully realized with a new strategy known as click chemistry. In this context, the oxidized nanocelluloses bearing alkyl groups (ONC-PR) were prepared by reacting amino groups of propargylamine (PR) with carboxyl groups of ONC. In parallel, PCL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 38 publications
(49 reference statements)
4
56
0
2
Order By: Relevance
“…Notably, we observed that, in the FTIR spectrum of NC, the O-H stretching band is shifted toward lower wave number (blue shifted) and become higher intense (hyper chromic) as endowed in Fig. 2a, confirming that during NC preparation, breakage of glucosidic bonds took place in pristine cellulose structure (Benkaddour et al 2013). This result evinces the successful preparation of NC.…”
Section: Resultssupporting
confidence: 48%
“…Notably, we observed that, in the FTIR spectrum of NC, the O-H stretching band is shifted toward lower wave number (blue shifted) and become higher intense (hyper chromic) as endowed in Fig. 2a, confirming that during NC preparation, breakage of glucosidic bonds took place in pristine cellulose structure (Benkaddour et al 2013). This result evinces the successful preparation of NC.…”
Section: Resultssupporting
confidence: 48%
“…Figure (b) shows a band around 2113 cm −1 , corresponding to the azide groups. When tosylated fibers reacted with sodium azide, the FTIR spectrum of azidated fiber showed the appearance of a new intense band typical of the azide groups, which clearly confirms that azide molecules covalently couple to the fiber chains . The FTIR spectrum of propargylated fiber in Figure (c) shows two new adsorption bands at 3286 cm −1 and 2119 cm −1 , corresponding to CH stretching and CC stretching, respectively, indicating the successful incorporation of terminal alkynes onto the fiber chains .…”
Section: Resultsmentioning
confidence: 88%
“…The strong hydrophilic nature of the fiber surface is the main reason why cellulose fiber is chemically modified . Cellulose fibers tend to agglomerate into bundles due to hydrogen bonds forming between the hydrophilic fibers, and they cannot be dispersed uniformly in most nonpolar polymer media . The most common approaches for cellulose modifications are esterification and etherification .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…160 This improvement is related to the rigidity of NC and the creation of accentuated fragility domains, which consequently increased the degree of crystallinity of the composites system. 161 However, the extent of mechanical reinforcement of NC in polycaprolactone matrix has been limited when its composition reached 12 wt%, due to the formation of nanocrystal aggregation during composites processing, derived from inter-particle interactions, which leads to the formation of weak points. This lack of intimate interface adhesion resulted in several irregular-shape microvoids within the composite.…”
Section: Mechanical Performance Of Nc/ Polycaprolactone Compositesmentioning
confidence: 99%